Performance of crossbred pigs with indigenous and Hampshire inheritance under a smallholder production system in the Eastern Himalayan hill region - Kadirvel, Govindasamy; Devi, Yumkhaibam Sovarani; Naskar, Syamal; Bujarbaruah, K. M.; Khargariah, Gutum; Banik, Santanu; Singh, Ningthoujam Suraj; Gonmei, Chamniugongliu (Frontiers in Genetics, 2023)
Pig productivity is very low in the Eastern Himalayan hill region due to the poor performance of local pigs. To improve pig productivity, it was decided to develop a crossbred pig of Niang Megha indigenous and Hampshire as an exotic germplasm. The performance of crossbred pigs with different levels of Hampshire and indigenous inheritance—H-50 × NM-50 (HN-50), H-75 × NM-25 (HN-75), and H-87.5 × NM-12.5 (HN-87.5)—was compared for their performance to find a suitable level of genetic inheritance. Among the crossbreds, HN-75 performed better in terms of production, reproduction performance, and adaptability. Inter se mating and selection were carried out on six generations of HN-75 pigs, and genetic gain and trait stability were evaluated and released as a crossbred. These crossbred pigs attained body weights of 77.5–90.7 kg by 10 months of age, with FCR of 4.3:1. Age at puberty was 276.66 ± 2.25 days, and average birth weight was 0.92 ± 0.06 kg. Litter size at birth and weaning were 9.12 ± 0.55 and 8.52 ± 0.81. These pigs have good mothering abilities with a weaning percentage of 89.32 ± 2.52%, good carcass quality, and consumer preference. The lifetime productivity for an average of six farrowings/sow showed a total litter size at birth of 51.83 ± 1.61 and total litter size at weaning of 47.17 ± 2.69. In a smallholder production system, the crossbred pigs showed a better growth rate and a higher litter size at birth and at weaning than average local pigs. Hence, the popularization of this crossbreed would enhance the production, productivity, livelihood, and income of the regionʼs farmers.